Preliminary Fusion Testing Between Whole Young Colonies of Coptotermes gestroi (Isoptera: Rhinotermitidae) - Guaraldo, A. C. [UNESP]; Costa-Leonardo, A. M. [UNESP] (California State University, 2009)
Everyyear in Brazil, colonies of the exotic termite Coptotermes gestroi increase their production of alates, which is the caste responsible for the foundation of new colonies. Colonies of this invasive species have huge populations, and their economical impacts have increased in urban areas during recent years. To simulate the meeting of neighboring colonies in field situations, we arranged intercolony interactions in the laboratory. Additionally, we exchanged one king or queen between colonies to observe how termites react to foreign reproductives. After 15 days of interactions, the mixed colony showed survival of both queens in 80% of the replicates and death of one king in 100% of the replicates. The present study also demonstrated tolerance of C gestroi colonies to foreign reproductives. The low agonism of the neuter caste (workers and soldiers) in the mixed colonies and the stability of the termite populations confirm the fusion of C. gestroi colonies. Probably, the few introductions of this species in Brazil resulted in populations of C. gestroi that are genetically very similar with high inter-colony relatedness.
Keywords: agonism; colony interactions; subterranean termites